If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 8 + 7x = 48 Combine like terms: -2 + 8 = 6 6 + 7x = 48 Solving 6 + 7x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 7x = 48 + -6 Combine like terms: 6 + -6 = 0 0 + 7x = 48 + -6 7x = 48 + -6 Combine like terms: 48 + -6 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| 6x-3(x-8)=9 | | -8x(-5)= | | Kx+Ly=mforY | | 4(3m-6)=9m+8 | | -6.4= | | K^2+7k-16=0 | | 5(2t+4)-4=19+7 | | y=8+19 | | 24=4+6+y+6 | | -5(4b+4)+(21b-6)=0 | | 13.7-4.7=9.9+8.1t | | 2x+8=x+21 | | 4n+15=45-2n | | 14.7t-4.7=9.9+8.1t | | 3=b+4 | | 3x-4=-2x+23 | | 8x-2=5x+8 | | 5y-13=-7y+37 | | -5x+2=4x+11 | | 27=3+7+y+7 | | 16+2y=64 | | y=1.7*12+89 | | (-4x)/(x+7)-(8)/(x+7) | | 5x-4+4x+3x+6=38 | | 2w=4 | | b(2)+24=8 | | m+9=-34 | | 15x-4+9x+3+12x+5=40 | | 15x-4+9x+3+12x+5=40 | | 95.8=1.7x+89 | | m+9=34 | | 24+4h=10 |